Control en la gestión de ingresos y gastos de Exillantas S.A. - Alarcón Zúñiga, Erick Santiago (2021)
At present it is vitally important to have order and control over what is seen and perceived, as with the actions that are carried out in this regard. Companies have to continuously adapt to the environment imposed by the market in which they are inserted, therefore, control over information is essential to make good decisions and stay current in said market ecosystem, which is why it has been taken as a particular case to the Company Exillantas SA To carry out an exhaustive analysis of their income and expenses obtained during the period from 2019 to 2020, To carry out this case study, an interview questionnaire was applied to the personnel in charge of keeping the records and controls thereof, giving as A poor management of them resulted, this being reflected in the debts that it maintains to date, obtaining a favorable response from the personnel of the company in question, collaborating with the answers to each of the questions asked in the survey. For the technical analysis of this case study, the main income and expenses of the company will be taken into consideration, the same that will go through a descriptive statistics process that will allow us to show the behavior of the variables, in addition to that, the statistics will also be present Inferential that will allow us to propose several hypotheses, it should be noted that, finally, it is important to note that this project is presented to comply with the requirements demanded by the Technical University of Babahoyo in the degree process for the Engineering in Accounting and Auditing career.